Confirmed microsporidial graft infection in a HIV‐negative renal transplant recipient: A case report and review of the literature. Issue 3 (10th April 2018) - Brown, M.; Longano, A.; Dendle, C.; Polkinghorne, K.R.; Kanellis, J.
Abstract: Microsporidia are intracellular organisms most commonly known to cause opportunistic infection in patients with human immunodeficiency virus (HIV). There have been several case reports of infection in solid organ and bone marrow transplant recipients. Here, we report a case of a non‐HIV–infected renal transplant patient with microsporidiosis of the renal tract associated with acute graft dysfunction. We also review the literature of 12 previously reported cases of microsporidiosis in patients with renal transplants who had described graft involvement. We review the pattern of illness as well as the common renal biopsy features when microsporidial infection is associated with renal graft infection.